Análisis de los efectos adversos post vacunación contra el covid-19 en adultos a través de una revisión bibliográfica - Ramírez Miguez, Tania Ibett (2025)
Introduction: With the advent of the COVID - 19 pandemic, there was an urgent need to design strategies to mitigate the morbidity and mortality caused by the virus, one of the most promising of which was mass vaccination. However, the relative haste in the development and testing of the different vaccines against COVID - 19 generated uncertainty and doubts in the population due to the diversity of adverse reactions generated by inoculation. Objective: To analyze the main post - vaccination adverse effects against Covid - 19 in the adult population. Materials and methods: This was a literature review study with a qualitative approach that included digital documents from: PubMed, Scielo, Elsevier, Google Scholar and official public health agencies. Updated information on COVID-19 post - vaccination adverse effects were included in the review. Results: Eighteen literature sources were included and most of them assumed that the adverse effects of inoculation for COVID - 19 were: headache, muscle pain, fatigue, fever and malaise of mild to moderate intensity. Serious adverse effects were minimal and related to comorbidities. Conclusion: Vaccination against Covid - 19 causes generally mild adverse effects which are indicative of the body acquiring immunity (antigen) and preparing itself to cope with the virus, thus reducing the risk of morbidity and mortality from this cause.